Area and population of the Brazilian savanna - Pereira, Geraldo; Aguiar, Jozeneida Lúcia P. de; Moreira, Lucimar; Bezerra, Heleno da S. (Pesquisa Agropecuaria Brasileira, 1997)
This research was developed in order to estimate the area and population of continuous Cerrado (Savanna). The Cerrado area was delimited in each municipality, since 34% of the municipalities studied are also located in other regions. Participation index (Cerrado area/total area) of each municipality was estimated by empirical technique incorporated in the Geographical Information System (SGI) developed by the Instituto de Pesquisas Espaciais (INPE). The area of 2,064,676 km2 and population of 21,064,010 people in 1991 were estimated using the index in this research.